Cryptography : Infosec pro guide - Oriyano, Sean-Philip (Infosec pro guide, 2013)
New in the Secure Beginner's Guide series, this complete, practical resource for security and IT professionals presents the underpinnings of cryptography and features examples of how security is improved industry-wide by encryption techniques.